A Study on Bacteriological Profile and Their Antibiogram of Community-Acquired Pneumonia in a Tertiary Care Teaching Hospital - Rajasekhar, Koppada (Asian Journal of Medical Research, 2020)
Background: Community-acquired pneumonia (CAP) is an acute infection of the lower respiratory tract and the most common type of lung infection that occurs outside of the hospital or within 48 hours after admission. CAP is one of the most common causes of hospitalization among infectious diseases worldwide, resulting in high fatality rates and large healthcare costs.[1-3] Aim: To study the Bacteriological profile of Community-Acquired Pneumonia and their Antibiogram, in patients. Objectives:1. To know the most prevalent Bacterial agents associated with CAP.2. To study the susceptibility pattern of the organisms isolated from these cases. 3. To correlate the risk factors and co-morbid conditions with the occurrence of CAP. Subjects and Methods: A prospective hospital-based observational study. Study area: Department of Microbiology, Guntur Medical College, Guntur, Andhra Pradesh. Study Period: 1 year. Study population: Suspected Community-Acquired Pneumonia patients who attended the Patient Department of General Medicine. Sample size: The study consisted of 500 subjects. Sampling method: Simple random technique. Sample collection: Sputum samples were collected from the patients before the initiation of antibiotics, under aseptic precautions. Early morning sputum samples were preferred whenever possible. Patients were asked to brush their teeth or rinse their mouths with water before coughing out the sputum sample. A deeply coughed-out sputum sample was collected in a sterile screw-top plastic container. A detailed history was taken, clinical parameters were noted, and Chest X-ray and routine investigations were carried out. Results: Streptococcus pneumoniae was 100% susceptible to Amoxicillin plus clavulanic acid and Vancomycin, followed by Cefotaxime, Azithromycin and Levofloxacin with 85.88%, 81.13% and 77.61% susceptible respectively and in ampicillin 32.96%. Conclusion: Pneumonia has increased in prevalence due to a lack of early detection and antibiotic resistance. The prevalence of Gram-negative bacteria as an etiological factor has also risen dramatically. According to this study, the majority of the organisms are resistant to third-generation cephalosporins. Further research should focus on how initial medication is administered in pneumonia patients.